1 sinx=t 2t²+t-1=0 D=1+8=9 t1=(-1-3)/4=-1⇒sinx=-1⇒x=-π/2+2πk,k∈z t2=(-1=30/4=1/2⇒sinx=1/2⇒x=π/6+2πk U x=5π/6+2πk,k∈z 2 2(1-sin²x)=3sinx+2 2sin²x+3sinx=0 sinx(2sinx+3)=0 sinx=0⇒x=πk,k∈z sinx=-1,5<-1 нет решения 3 разделим на cos²x 3tg²x-13tgx+4=0 tgx=t 3t²-13t+4=0 D=169-48=121 t1=(13-11)/6=1/3⇒tgx=1/3⇒x=arctg1/3+⇒k,k∈z t2=(13+11)/6=4⇒tgx=4⇒x=arctg4+⇒k,k∈z 4 tgx=t t²-t+3=0 D=1-12=-11<0 нет решения 5 4сosx-(1-сos²x)-4=0 cos²x+4cosx-5=0 cosx=t t²+4t-5=0 t1+t2=-4 U t1*t2=-5 t1=-5⇒cosx=-5<-1 нет решения t2=1⇒cosx=1⇒x=2πk,k∈z
sinx=t
2t²+t-1=0
D=1+8=9
t1=(-1-3)/4=-1⇒sinx=-1⇒x=-π/2+2πk,k∈z
t2=(-1=30/4=1/2⇒sinx=1/2⇒x=π/6+2πk U x=5π/6+2πk,k∈z
2
2(1-sin²x)=3sinx+2
2sin²x+3sinx=0
sinx(2sinx+3)=0
sinx=0⇒x=πk,k∈z
sinx=-1,5<-1 нет решения
3
разделим на cos²x
3tg²x-13tgx+4=0
tgx=t
3t²-13t+4=0
D=169-48=121
t1=(13-11)/6=1/3⇒tgx=1/3⇒x=arctg1/3+⇒k,k∈z
t2=(13+11)/6=4⇒tgx=4⇒x=arctg4+⇒k,k∈z
4
tgx=t
t²-t+3=0
D=1-12=-11<0
нет решения
5
4сosx-(1-сos²x)-4=0
cos²x+4cosx-5=0
cosx=t
t²+4t-5=0
t1+t2=-4 U t1*t2=-5
t1=-5⇒cosx=-5<-1 нет решения
t2=1⇒cosx=1⇒x=2πk,k∈z